Designing Foldamer–Foldamer Interactions in Solution: The Roles of Helix Length and Terminus Functionality in Promoting the Self‐Association of Aminoisobutyric Acid Oligomers. Issue 48 (3rd October 2014) - Pike, Sarah J.; Diemer, Vincent; Raftery, James; Webb , Simon J.; Clayden, Jonathan
Abstract The biological activity of antibiotic peptaibols has been linked to their ability to aggregate, but the structure–activity relationship for aggregation is not well understood. Herein, we report a systematic study of a class of synthetic helical oligomer (foldamer) composed of aminoisobutyric acid (Aib) residues, which mimic the folding behavior of peptaibols. NMR spectroscopic analysis was used to quantify the dimerization constants in solution, which showed hydrogen‐bond donors at the N terminus promoted aggregation more effectively than similar modifications at the C terminus. Elongation of the peptide chain also favored aggregation. The geometry of aggregation in solution was investigated by means of titrations with [D6]DMSO and 2D NOE NMR spectroscopy, which allowed the NH protons most involved in intermolecular hydrogen bonds in solution to be identified. X‐ray crystallography studies of two oligomers allowed a comparison of the inter‐ and intramolecular hydrogen‐bonding interactions in the solid state and in solution and gave further insight into the geometry of foldamer–foldamer interactions. These solution‐based and solid‐state studies indicated that the preferred geometry for aggregation is through head‐to‐tail interactions between the N and C termini of adjacent Aib oligomers.